Personality Traits and Financial Well-Being of College Students in Davao City - Obenza, Brandon; Tabac, Charles Emyrrhson; Estorba, Danica Rose; Baring, Aliane; Rizardo, Janna Paula; Badayos, Christian Jay; Zaragoza, Antoinette Paula; Dela Cruz, Princess Sally (International Journal of Applied Research and Sustainable Sciences, 2024)
This study examined the predictive power of personality traits (extraversion, agreeableness, openness, conscientiousness, and neuroticism) on the financial well-being of college students in Davao City. In addition, this study used a correlational-quantitative design. 307 college students from various public and private institutions in the City participated in the online survey via Google forms. Hypotheses were tested using regression analyses in SmartPLS 4.0 software by the researchers. The findings of the study show that only extraversion (R=0.205, p-value=0.002) and neuroticism (R=0.181, p-value=0.001) are significantly and positively associated with financial well-being. On the other hand, there was no discernible correlation found in the hypothesized paths between agreeableness, conscientiousness, and openness, toward financial well-being. The regression model’s R² value of 0.130 implies that the personality traits can explain 13% of the variance in college students’ financial well-being. Finally, the study has provided insights for creating targeted interventions and initiatives that will improve college students’ overall well-being alongside financial literacy.